Military and technical cooperation evolution of the Russian Federation in the global economy - D. A. Repnikov (Управление, 2023)
The current global market for armaments and military equipment in the second half of the 20th century has went through several transformative stages of its development and has now reached a qualitatively new evolution level. The aim of the study is to analyse the key trends in changing Russia’s positions in the global arms trade, including an assessment of its export and investment potential in defence industry, and opportunities for cooperation with key regional and global partners. It has been shown, that the international competitiveness of the Russian defence industry and the development of its military-technical cooperation with foreign countries continue to be affected by the specific conditions of the industry, in particular: weak susceptibility to major changes in the arms trade; high role of state protectionism; international technology transfer; globalisation of the world economy as a whole. An important role in shaping the current image of the military-technical cooperation is played by the dynamic and constant rearmament of the army, offset services and the partnerships cooperative networks’ formation, on which the flexibility and adaptability of the external economic component of defence industry operations depend. At present, the development of Russia’s armaments and military equipment trade will be mainly driven by the restoration of its lost positions on the global market.